Needles, China Cups, Books, and the Construction of the Victorian Feminine Ideal in Rhoda Broughton’S Not Wisely, but too Well and Elizabeth Gaskell’S North and South - Setecka, Agnieszka (Studia Anglica Posnaniensia, 2013)
Considering Victorian presentation of women as angelic, that is, spiritual, beings, it is rather surprising how much their presence was manifested by material objects. Baskets of needlework, tea equipage and novels lying around in a parlour were an unmistakable sign of the house being occupied by women. Indeed, my contention is, the objects did not clutter Victorian interiors, either real or imagined, merely for practical reasons or to produce the “reality effect.” They are a material representation of the immaterial and function as metaphors for angelic women’s spiritual qualities. Rather than functioning merely as details to enhance the illusion of the real (and thus as elements of style) or simply reflecting the Victorian world (and thus as empty forms), material objects are essential in constructing a middle-class (feminine) identity. My paper concentrates on Rhoda Broughton’s Not wisely, but too well and Elizabeth Gaskell’s North and South with an attempt to show how objects help construct a feminine ideal and, simultaneously, reveal the ideal to be just a construction. Broughton’s Kate Chester and Gaskell’s Margaret Hale find themselves in situations where their middle-class status might be compromised. Still, they both manage to reassert their position through effectively manipulating the signs of middle-class respectability. The “flimsy and useless” things they surround themselves with point to their “essentially feminine” qualities. Yet, the very superfluity of the objects reveals their relation to the characters’ economic status. They are, then, the site where the material and immaterial meet, where the borders between the economic world and the domestic world blur.